Unveiling a novel S-Box strategy: The dynamic 3D scrambling approach - Nayeem Ahmad Khan; Abdulbasid Banga; Taher M. Ghazal; Bayan Alabdullah; Nadeem Iqbal; Ahmad Alshamayleh; Atif Ikram; Hossam Diab (PLoS ONE, 2025)
A close study about the varied anatomies of the S-Box algorithms published in the literature indicates that no attempt has been made using the notion of 3D. To cement the more cryptographic security, this research article ventures to present a novel S-Box algorithm exploiting the notion of 3D. First of all, the algorithm initializes a 3D scrambled S-Box with the value of -1. After that, a 1D array is initialized with all the numbers of the potential S-Box. Now, the values placed in the 1D array are inserted randomly to the different cells of the 3D scrambled S-Box until all the numbers from the 1D array are not shifted. The way, the S-Box has been developed bears an ample promise to raise the inherent non-linearity of the required S-Box which, in turn, equips the S-Box to defy the potential cryptanalytic threats from the hackers and other adversaries. Lorenz chaotic system has been employed to produce streams of random numbers. Through rigorous analysis and experimentation, we demonstrate the efficacy of our approach in enhancing cryptographic security, offering robust protection against various cyber threats. Our research contributes to the advancement of S-Box design methodologies, providing a promising avenue for strengthening encryption algorithms in contemporary cryptographic systems. Potential real-world applications include secure communications in IoT devices, encryption in smart grid infrastructures, and data protection in medical imaging systems.